Forest Types Studies in Manipur - Deb, D. B. (Indian Forester, 1960)
No systematic study of the forests of Manipur was ever attempted. The present paper is based on a study of Manipur forests for about five years. It attempts at an identification and classification of forest types. In classification the Clementsian system has been followed in general with the acceptance of Bor's views on nomenclature modified still further. Topographical features, hill ranges, river system, lakes and jheels of the territory have been described. Factors determining vegetation types-climate, geology, soil, biotic and physiographic factors have been discussed. Ten climatic units included in eight formations have been described and influences of climatic, edaphic and biotic factors on them have been discussed.